Raw Material Supply to Shrimp Freezing Plants: Some Significant Aspects - RAO, K KRISHNA; LAKSHMANAN, P T; AGARWAL, ANIL; CHAKRABORTY, R (Fishery Technology, 2017)
The shrimp processing plants located at any particular place receive their raw material supplies from local and outside centres. The raw material received, the form in which it was received, the relative contribution by local and outside centres and the seasonal variation in the supplies were studied with respect to the shrimp processing plants located at three places - Cochin, Veraval and Kakinada.